(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we prove the existence and uniqueness of the fixed point for T-contraction mapping under the concept of c-Distance in cone metric spaces with solid cone. The obtained results extend and generalize well known comparable results in the literature.